Deterministic Integration of hBN Emitter in Silicon Nitride Photonic Waveguide. Issue 6 (7th May 2021) - Elshaari, Ali W.; Skalli, Anas; Gyger, Samuel; Nurizzo, Martin; Schweickert, Lucas; Esmaeil Zadeh, Iman; Svedendahl, Mikael; Steinhauer, Stephan; Zwiller, Val
Abstract: Hybrid integration provides an important avenue for incorporating atom‐like solid‐state single‐photon emitters into photonic platforms that possess no optically‐active transitions. Hexagonal boron nitride (hBN) is particularly interesting quantum emitter for hybrid integration, as it provides a route for room‐temperature quantum photonic technologies, coupled with its robustness and straightforward activation. Despite the recent progress of integrating hBN emitters in photonic waveguides, a deterministic, site‐controlled process remains elusive. Here, the integration of selected hBN emitter in silicon nitride waveguide is demonstrated. A small misalignment angle of 4° is shown between the emission‐dipole orientation and the waveguide propagation direction. The integrated emitter maintains high single‐photon purity despite subsequent encapsulation and nanofabrication steps, delivering quantum light with zero delay second order correlation function g ( 2 ) ( 0 ) = 0.1 ± 0.05 . The results provide an important step toward deterministic, large scale, quantum photonic circuits at room temperature using atom‐like single‐photon emitters. Abstract : A deterministic process for integrating room‐temperature hexagonal boron nitride (hBN) single photon source in silicon nitride waveguides is presented. The encapsulated emitter maintains high single‐photon purity delivering quantum light with zero delay second order correlation function g ( 2 ) ( 0 ) = 0.1 ± 0.05 . The result is an important step toward deterministic, large scale, quantum photonic circuits at room temperature using atom‐like quantum emitters.